2012
DOI: 10.1016/j.jvs.2011.10.122
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric artery complications during angioplasty and stent placement for atherosclerotic chronic mesenteric ischemia

Abstract: Objective The purpose of this study was to describe the incidence, management, and outcomes of mesenteric artery complications (MACs) during angioplasty and stent placement (MAS) for chronic mesenteric ischemia (CMI). Methods We retrospectively reviewed the clinical data of 156 patients treated with 173 MAS for CMI (1998–2010). MACs were defined as procedure-related mesenteric artery dissection, stent dislodgement, embolization, thrombosis, or perforation. End points were procedure-related morbidity and deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 17 publications
0
44
0
9
Order By: Relevance
“…Rarer are perforation of the target vessels (19%), dissections (10%), as well as acute stent dislocations and acute in-stent thrombosis (10%) [22]. A significant drawback of ET are the early and late outcomes, which are worse compared to open repair, although they are not relevant for the short-term prognosis of AMI [23].…”
Section: Are Endovascular Techniques a Reasonable Treatment Option?mentioning
confidence: 99%
“…Rarer are perforation of the target vessels (19%), dissections (10%), as well as acute stent dislocations and acute in-stent thrombosis (10%) [22]. A significant drawback of ET are the early and late outcomes, which are worse compared to open repair, although they are not relevant for the short-term prognosis of AMI [23].…”
Section: Are Endovascular Techniques a Reasonable Treatment Option?mentioning
confidence: 99%
“…Oderich et al reported 7% major complication rate in 156 patients who underwent mesenteric artery angioplasty and stenting, mostly (98%) with balloon expandable bare metal stents (BMS). Six patients had distal mesenteric embolization, three with jejunal branch perforation, two with isolated dissection, two with stent dislodgement associated with severe SMA angulation and one with stent thrombosis …”
Section: Discussionmentioning
confidence: 99%
“…Parenteral nutrition is warranted because of the long period of malnutrition [5,28] . Open revascularization (OR) and endovascular revascularization (ER) are the alternative modalities of treatment in patients with CMI [50][51][52] . ER appears to have lower postoperative mortality and morbidity rates and shorter intensive care unit and hospital stay.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…An embolic protection device may be considered in the presence of a large thrombus burden. However, there is limited evidence showing its efficacy during ER for CMI [37,50,51] .…”
Section: Therapeutic Approachmentioning
confidence: 99%